The valley of fear and selected cases - Doyle, Arthur Conan, Sir, 1859-1930. (London ; New York : Penguin, 2001)
A man called Douglas has received a bullet in the head. Sherlock Holmes has deciphered a secret message warning him of Douglas's danger - too late. When he arrives at Douglas's home he finds a bizarre series of clues: the victim's branded arm, the theft of his wedding ring and a mysterious calling card. Scotland Yard is stumped, but Holmes, who has detected the evil presence of Moriarty in this crime, has some ideas of his own.
Valley of fear -- Selected cases from The return of Sherlock Holmes: Empty house ; Dancing men ; Black Peter ; Charles Augustus Milverton ; Six Napoleons ; Abbey grange -- From His last bow: Adventure of the Bruce-Partington plans ; Adventure of the dying detective ; Disappearance of Lady Frances Carfax ; His last bow.
Keywords: Detective and mystery stories, English; Watson, John H. -- (Fictitious character) -- Fiction; Holmes, Sherlock -- Fiction; Private investigators -- England -- Fiction; Mystery fiction